Pemanfaatan Media Teks Fiksi Dan Mentimeter Dalam Peningkatan Literasi Bahasa Sastra Dan Numerikal Pada Siswa/I SMA Swasta Tri Sakti Lubuk Pakam - Sahat Taruli Siahaan; Dimpu P.Simanullang; Parlaungan Simamora; Jernih Jelita Pandiangan; Sonira Agita Sinaga (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Community Service (PkM) Faculty of Teacher Training and Education (FKIP) HKBP Nomensen University Medan is a service program carried out by a team of students and DPL lecturers with the title "Utilization of Fiction Text Media and Mentimeter in Increasing Literacy in Literary and Numerical Language in High School Students Private Tri Sakti Lubuk Pakam”. The Community Service Program (PKM) of the Faculty of Education and Teacher Training is implemented by the university in an effort to increase knowledge in students to gain added value and as a means of increasing insight and experience which can trigger broader knowledge for students. This activity aims to improve student character by using fictional text media and time meter in learning Indonesian and Mathematics, especially for TRI SAKTI Lubuk Pakam Private High School students, to be able to apply and receive Indonesian and Mathematics tutoring well, and be able to demonstrate knowledge Using the Mentimeter application or characters on students after participating in PKM community service activities can help the community, especially students, in completing missed lessons.